Research on spiral movement robot - Mohd Hanafi, Muhammad Sidik (2012)
Surveillance cameras are video cameras used for the purpose of observing an area.They are often connected to a recording device or IP network, and may be watched by a security guard or law enforcement officer. Cameras and recording equipments used to be relatively expensive and required human personnel to monitor camera footage, but analysis of footage has been made easier by automated software that organizes digital video footage into a searchable database, and by video analysis software. The amount of footage is also drastically reduced by motion sensors which only record when motion is detected. With cheaper production techniques, surveillance cameras are simple and inexpensive enough to be used in home security systems, and for everyday surveillance,and that's why now there are a lot of people installed security camera to protect their family and properties.